COMPARISON ANALYSIS OF CARGO SERVICE BETWEEN PT. GARUDA INDONESIA AND PT. LION AIR GROUP - Montung, Leidy Priscyla; Tumbuan, Willem J. F. A.; Rumokoy, Farlane S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: In companies engaged in the field services such as delivery goods that are currently needed by many people to deliver goods to various places far away so that it can be easily reached and fast. In delivery goods there are 5 things that need to be considered, namely price, trust, value, time and location for each company engaged in freight forwarding services.This study aims to analyze the comparison of cargo services between PT. Garuda Indonesia and PT. Lion Air Group in Manado. The population is peoples who using cargo service from Manado to another places, the sample is 100 respondents (50 respondents from PT. Garuda Indonesia and 50 respondents from PT. Lion Air Group). This study uses Pearson Correlation and for the analytical method used is quantitative by using the Independent Sample T Test analysis technique. The result of the research shows that PT. Lion Air Group has more dominant on price and location comparison between PT. Garuda Indonesia and last PT. Garuda Indonesia has more dominant on trust, value, and time comparison that PT. Lion Air Group. Companies more improve their service quality so they can provide better.Keyword: comparison and cargo service